1988
DOI: 10.1017/s0043174500074439
|View full text |Cite
|
Sign up to set email alerts
|

Wild Oat (Avena fatua) and Spring Barley (Hordeum vulgare) Growth and Development in Monoculture and Mixed Culture

Abstract: Barley (Hordeum vulgareL. ‘Advance’) and wild oat (Avena fatuaL. # AVEFA) were grown in the field in monoculture and mixed culture (additively) to compare their seasonal growth and development. Barley and wild oat tiller and tiller head production were reduced by the interference (higher density) of the other species. Plant height of either species was not affected by interference of the other. Wild oat biomass was reduced more and at an earlier growth stage (two to three tillers) than was barley biomass (head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…The critical weed:barley interference period study carried out in 1996–97 showed clearly that interference between weed and barley started in early April, in agreement with observations reported by Morishita & Thill (1988). The lower growth rate (slope b) determined from the regression equations for cvs Klipper and Plaisant grown in competition with either weed species, shows that both weeds were more competitive against these two cultivars and this was the reason for their greatest growth reduction.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The critical weed:barley interference period study carried out in 1996–97 showed clearly that interference between weed and barley started in early April, in agreement with observations reported by Morishita & Thill (1988). The lower growth rate (slope b) determined from the regression equations for cvs Klipper and Plaisant grown in competition with either weed species, shows that both weeds were more competitive against these two cultivars and this was the reason for their greatest growth reduction.…”
Section: Discussionsupporting
confidence: 86%
“…ludoviciana caused 19–52% yield losses of four barley cultivars. Morishita & Thill (1988) reported that yield and ear number of spring barley were significantly reduced by the presence until harvest of 150 A. fatua plants m −2 . Afentouli & Eleftherohorinos (1996) also found that the presence of either P. minor or P. brachystachys Link until harvest did not have any significant effect on yield components of cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild oat is adapted to a wide range of geographical areas and climates and is one of the 12 most successful colonizing species in the world (Allard 1965). Morishita and Thill (1988) estimated that 11,000,000 ha in the United States contain wild oat populations that are responsible for causing economic losses of 1 billion dollars.…”
mentioning
confidence: 99%
“…In Alberta, Canada, wheat (Triticum aestivum L.) yield was reduced between 55 and 85% when wild oat emerged prior to wheat emergence (O'Donovan et al 1985). Yield losses in barley from competition with wild oat ranged from 30 to 72%, depending on wild oat density (Chancellor and Peters 1976; Morishita and Thill 1988;Wilson and Peters 1982). Lack of wild oat control also reduces harvesting efficiency and the quality of cereal crops.…”
mentioning
confidence: 99%